Health financing reform in Kenya- assessing the social health insurance proposal - Carrin, Guy; James, Chris; Adelhardt, Michael; Doetinchem, Ole; Eriki, Peter; Hassan, Mohammed; Onsongo, Joyce A. (African journals online, 2007)
Kenya has had a history of health financing policy changes since its independence in 1963. Recently, significant preparatory work was done on a new Social Health Insurance Law that, if accepted, would lead to universal health coverage in Kenya after a tr&nsition period. Questions of economic feasibility and political acceptability continue to be discussed, with stakeholders voicing concerns on design features of the new proposal submitted to the Kenyan parliament in 2004. For economic, social, political and organisational reasons a transition period will be necessary, which is likely to last more than a decade. However, important objectives such as access to health care and avoiding impoverishment due to direct health care payments should be recognised from the start so that steady progress towards effective universal coverage can be planned and achieved.